Development of next generation nanomedicine-based approaches for the treatment of cancer: we've barely scratched the surface. (1st November 2021) - Tracey, Shannon R.; Smyth, Peter; Barelle, Caroline J.; Scott, Christopher J.
Abstract : Interest in nanomedicines has grown rapidly over the past two decades, owing to the promising therapeutic applications they may provide, particularly for the treatment of cancer. Personalised medicine and 'smart' actively targeted nanoparticles represent an opportunity to deliver therapies directly to cancer cells and provide sustained drug release, in turn providing overall lower off-target toxicity and increased therapeutic efficacy. However, the successful translation of nanomedicines from encouraging pre-clinical findings to the clinic has, to date, proven arduous. In this review, we will discuss the use of nanomedicines for the treatment of cancer, with a specific focus on the use of polymeric and lipid nanoparticle delivery systems. In particular, we examine approaches exploring the surface functionalisation of nanomedicines to elicit active targeting and therapeutic effects as well as challenges and future directions for nanoparticles in cancer treatment.